(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The paper undertakes a Meta-analysis on research done on the topic of reverse logistics and the effect it bears on the Kenyan remanufacturing sector, while considering the moderating effect of the regulatory environment as a result of limited adoption of the practice and studies undertaken on the area of interest. The study is pegged on the resource-based view that puts emphasis on the capabilities of the firms in reverse logistics and transport cost economics, which explains the challenges in governance of return networks. The paper reviews literature systematically through a meta-analysis methodology following the PRISMA guidelines, where articles are searched in prestigious academic databases. The research obtained 80 articles from SAGE, Science Direct, and Wiley between periods of 2020 and 2026. Duplicates and publications that were not based on reverse logistics, not empirically undertaken, and publications from predatory journals were eliminated, leaving 30 that were further subjected to the inclusion criteria, leaving 14 peer-reviewed articles whose empirical and theoretical findings were used to evaluate the effect of reverse logistics on the efficiency of Kenyans' remanufacturing supply chain. The study adopted the Hunter-Schmidt method to synthesize correlation coefficients from multiple studies. The findings of the study support the theoretical framework that links reverse logistics and supply chain efficiency in the remanufacturing sector on average (r=0.42) globally, in developed countries (r) =0.60, In Kenya, the r coefficient is below 0.42, showing a weak correlation, as infrastructure and the informal sector dominance, limits the adoption of reverse logistics from reaching its preferred potential. The moderation analysis determined that the regulatory environment, in terms of policy regulations and laws (average r of 0.51), moderates the relationship between reverse logistics and supply chain efficiency. The studies imply the existence of a need for the adoption of strategic regulations that target policy coherence, the incorporation of technology, and alignment of the stakeholders to enhance significant efficiency gains. The findings enrich and confirm the theoretical discourse on the manner in which the business environment interacts with the constructs of reverse logistics to drive efficiency in remanufacturing sector supply chains.